Sports journalism an introduction to reporting and writing - Stofer, Kathryn T.; Schaffer, James R. 1949-; Rosenthal, Brian A. (Rowman & Littlefield, 2019)
"Sports Journalism Second Edition introduces students to sports reporting careers and to the writing style, technology and social media skills sports writers and media relations professionals use. The book stresses the importance of basic writing fundamentals and high ethical standards, essential values for sports journalists"--